Vliv inokulace vybraných ektomykrohizních hub na růstové charakteristiky semenáčků dubu a buku. - Zíbarová, Lucie (Jihočeská univerzita, 2008)
Ectomycorrhizal inoculation proved to be an useful tool for promotig growth and survival of nursery seedlings, but little research of inoculation practices has been done in the Czech Republic so far. To fill this gap, effect of inoculation of Laccaria laccata and Russula ochroleuca on growth characteristic of beech and oak seedlings has been evaluated.
Influence of selected ectomycorrhizal fungi on growth characteristics of oak and beech seedlings.